Methane emissions from gathering and boosting compressor stations in the U.S. Supporting volume 1: Multi-day measurements of pneumatic controller emissions - Luck, Benjamin, author; Zimmerle, Daniel, author; Vaughn, Timothy, author; Lauderdale, Terri, author; Keen, Kindal, author; Harrison, Matthew, author; Marchese, Anthony, author; Williams, Laurie, author; Allen, Dave, author (Colorado State University. Libraries, 2019)
This study was part of a larger study (the Gathering Emission Factor, or "GEF") study [1] to develop activity and methane emission factors for EPA's Greenhouse Gas Inventory (EPA GHGI) using direct emission measurements at the device level on all classes of equipment found on gathering compressor stations. To accomplish this, Colorado State University (CSU) partnered with the engineering firm AECOM to assist with planning, logistics, field work and analysis. Nine midstream natural gas companies – Anadarko Petroleum, Equinor, DCP Midstream, Kinder Morgan, MarkWest Energy Partners, Pioneer Natural Resources, Southwestern Energy, Williams Companies Inc., and XTO Energy Inc. – acted as partners in the study, provided site access for measurements, and provided representatives to advisory committees. At all times, and with the encouragement of industry partners, CSU maintained control the sampling plan, analysis and reporting. This study documents one part of the larger study - emissions from pneumatic actuated valve controllers (PC).
Volume 1: Multi-day measurements of pneumatic controller emissions
Multi-day measurements of pneumatic controller emissions
Authors are from: Energy Institute at Colorado State University, AECOM, SLR Consulting, Fort Lewis College, and University of Texas, Austin, Texas, USA.
Keywords: pneumatics; methane; greenhouse gases; emission factors